The effectiveness of applied learning: an empirical evaluation using role playing in the classroom - Acharya, Harneel; Reddy, Rakesh; Hussein, Ahmed; Bagga, Jaspreet; Pettit, Timothy (Journal of research in innovative teaching & learning, 2019)
PurposeThe purpose of this paper is to evaluate the effectiveness of role playing as an applied learning technique for enhanced classroom experiences as compared to traditional lecture methods.Design/methodology/approachThis study uses the pre-test/post-test design to conduct experiments with several control and experimental groups. Subjects are graduate students in an MBA program at a private, non-profit university in a traditional classroom setting.FindingsStudents in the experimental group gained significantly more knowledge (post-test minus pre-test scores) – 45 percent higher – through participation in the role playing exercise as compared to the control group.Research limitations/implicationsThis study represents only a single educational discipline explored using a single role playing learning activity. Impacts on the long-term retention of the knowledge should be studied further.Practical implicationsEducators should enhance their classroom experience with more applied learning activities such as role playing in order to increase knowledge gain and potentially longer knowledge retention.Originality/valueThis study uses a customized role playing activity within a business curriculum as one of many applied learning techniques. The value to students was shown by significantly higher gain in knowledge while simultaneously enhancing their enjoyment of the classroom experience to potentially encourage further lifelong learning.